Nilai Tanah Kota Makassar Berbasis Rent-Bid Curve - Desi Tri Anita Sari; Ihsan Ihsan; Abdul Rachman Rasyid (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
The rapid development of the city and increasing population, has led to an increase in land requirements. Increasing land requirements will result in higher land values. Makassar City is one of the metropolitan cities that is currently experiencing a crisis of land availability. This happened because the high level of development in the Makassar City, so that demand for land values ​​to be increased. The purpose of this study was to find out and identify the land value of Makassar City based on Rent-Bid Curve. This study uses a library approach and field research. The library approach is done by reading theories relating to land values from the study literature, and used to obtain secondary data. Field research was conducted by observation to determine the conditions of land use in the Makassar City. The analytical method used by descriptive quantitative and qualitative, to describe the land value of Makassar City based on research variables. Spatial analysis was used to identify the land values ​​of Makassar City based Rent-Bid Curve on distance and land use. Correlation analysis was used to determine the relationship of distance and land value. The results of this study indicate that land value of Makassar City is influenced by distance, which is getting closer to the city center, the land value is higher. While the farther from the city center, land values is be the lower. In addition, land use also affects the land value in Makassar City, with the most influential land use is commercial.